2016
DOI: 10.1111/ajt.13843
|View full text |Cite
|
Sign up to set email alerts
|

Machine Perfusion of Donor Livers for Transplantation: A Proposal for Standardized Nomenclature and Reporting Guidelines

Abstract: With increasing demand for donor organs for transplantation, machine perfusion (MP) promises to be a beneficial alternative preservation method for donor livers, particularly those considered to be of suboptimal quality, also known as extended criteria donor livers. Over the last decade, numerous studies researching MP of donor livers have been published and incredible advances have been made in both experimental and clinical research in this area. With numerous research groups working on MP, various technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
120
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 108 publications
1
120
0
4
Order By: Relevance
“…Terms such as hypothermic, subnormothermic, or normothermic were frequently used to describe perfusion temperatures, and the absence of a standardized criterion to describe technical details led to great heterogeneity between studies. In 2016, a group of distinguished researchers in the field of liver preservation proposed a nomenclature of perfusion temperature ranges that facilitates the comparison of different studies, meta-analysis realization, and criteria homogenization [113]. Much work in this area has focused on liver perfusion, although the same broad concepts apply to other organs.…”
Section: Classification Of Perfusion Techniques Based On Preservationmentioning
confidence: 99%
See 2 more Smart Citations
“…Terms such as hypothermic, subnormothermic, or normothermic were frequently used to describe perfusion temperatures, and the absence of a standardized criterion to describe technical details led to great heterogeneity between studies. In 2016, a group of distinguished researchers in the field of liver preservation proposed a nomenclature of perfusion temperature ranges that facilitates the comparison of different studies, meta-analysis realization, and criteria homogenization [113]. Much work in this area has focused on liver perfusion, although the same broad concepts apply to other organs.…”
Section: Classification Of Perfusion Techniques Based On Preservationmentioning
confidence: 99%
“…The proposed cutoff point for HMP at 12°C is supported by the observation of numerous energy-dependent reactions of mitochondrial liver enzymes which exhibit significant rate changes at this temperature [113]. …”
Section: Classification Of Perfusion Techniques Based On Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex situ perfusion of donor livers, both in clinical o r e x p e r i m e n t a l a c t i v i t i e s , c a n b e p e r f o r m e d a t four different temperature ranges: (I) hypothermia (41). Studies using HMP are generally performed at temperatures ranging from 4 to 10 ℃ in order to decrease metabolism and enzymatic reactions rate in mammalian cells as low as 20% or less (42,43).…”
Section: Dcdmentioning
confidence: 99%
“…He is to be commended for this great achievement, which we consider a milestone in the history of organ transplantation. Even though the field of ex‐situ machine perfusion in organ transplantation is rapidly emerging, all currently used protocols still include periods of cold or warm ischemia before and after the period of machine perfusion 2. With their innovative surgical technique, He and colleagues have demonstrated that organ transplantation can be performed without any meaningful ischemia‐reperfusion (IR) injury, and they have taken machine perfusion to a different level.…”
mentioning
confidence: 99%